1995
DOI: 10.1021/jm00014a031
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Pharmacologic Activity, and Structure-Activity Relationships of a Series of Propafenone-Related Modulators of Multidrug Resistance

Abstract: A series of [(o-acylaryl)oxy]propanolamines have been prepared and evaluated for multidrug resistance-reverting activity in a human tumor cell model. Structure-activity relationship studies indicate that the phenylpropiophenone moiety as well as the substitution pattern at the nitrogen atom is crucial for activity of the compounds. Incorporation of the ether oxygen into a benzofuran substructure, which renders the compound an arylethanolamine, decreased biologic activity. Highest activity could be observed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
2

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 7 publications
1
53
0
2
Order By: Relevance
“…However, similar to quaternary compounds, propafenone analogs containing a tertiary nitrogen atom caused a shift in fluorescence when P-gp was reacted with the conformation-sensitive antibody UIC2 (S. Park and P. Chiba, unpublished observations). In addition, a number of studies from our group demonstrated that propafenones inhibit the transport of known P-gp substrates, including rhodamine 123, daunorubicin (Chiba et al, 1995;Ecker et al, 1999Ecker et al, , 2002, mitoxantrone, and vinblastine (S. Kopp and P. Chiba, unpublished observations). Photolabeling of plasma-membrane vesicles with the radioactive analog […”
Section: Resultsmentioning
confidence: 93%
“…However, similar to quaternary compounds, propafenone analogs containing a tertiary nitrogen atom caused a shift in fluorescence when P-gp was reacted with the conformation-sensitive antibody UIC2 (S. Park and P. Chiba, unpublished observations). In addition, a number of studies from our group demonstrated that propafenones inhibit the transport of known P-gp substrates, including rhodamine 123, daunorubicin (Chiba et al, 1995;Ecker et al, 1999Ecker et al, , 2002, mitoxantrone, and vinblastine (S. Kopp and P. Chiba, unpublished observations). Photolabeling of plasma-membrane vesicles with the radioactive analog […”
Section: Resultsmentioning
confidence: 93%
“…The permanently charged ammonium derivative GPV708 was obtained via methylation of the corresponding diethylamino-derivative (Chiba 1995). IR, MS, NMR spectroscopy and elemental analysis confirmed the structure of all novel compounds.…”
Section: Methodsmentioning
confidence: 85%
“…Synthesis of compounds GPV05 to GPV180 was achieved as described previously (Chiba et al 1995Tmej et al, 1998). Benzophenone derivatives were synthesized in analogy to the procedures for GPV317 and GPV319 as outlined in Scheme 1 (Tmej et al, 1998).…”
Section: Methodsmentioning
confidence: 99%
“…The design and synthesis of propafenone-type compounds including the photo-affinity ligands has been described previously (Chiba et al, 1995(Chiba et al, , 1996Ecker et al, 2002). Structures were confirmed by IR, mass spectroscopy, NMR spectroscopy, and elemental analysis.…”
Section: Methodsmentioning
confidence: 99%